A Phonological Study of the Tegem Language - Ali, Ahmed Sosal Altayeb Mohammed (Linguistics, 2020)
This study describes the phonological structure of the Tegem language, a little-known Niger-Kordofanian language spoken by around 2000 people in Sudan. The research follows the basic linguistic theory in identifying the segments, investigating their phonotactic pattern, and identifying their functional role in meaning distinction. The study is based on lexical items collected from two Tegem language speakers via wordlists elicitation sessions. That provides the core basis for a detailed foundational description of the phonetic and phonological features of consonants, consonant sequences, vowels, syllables, and tones in Tegem. The description includes a brief account of relevant morphophonemic phenomena such as the voicing assimilation, consonant labialization and noun class sound alternations. Tegem consonants and vowels phonemes are categorized into two and three categories respectively. The consonants comprises of five obstruent and nine sonorant phonemes out of 20 phones. The vowels include four front, two central, and four back vowels phonemes out of 12 phones. Both the consonants and vowels are very common to occur in a phonologically (and morphologically) complex clusters. There are phonotactic constrains on such sequences conditioned by the environment where they occur. The study explored those sequences as bisegmental structures of adjacent segment sequences. The suprasegmental analysis found six closed and seven open syllables in Tegem where the monosyllabic lexemes of CVC and CVV are the most salient among its 13 syllable types. The research also recognized a pattern of backness (±back) vowel harmony in the disyllabic nouns and adjectives. The syllable is determined as the bearing unit of the lexical tone in Tegem, i.e. change in the syllable tone is contrastive. The lexical tones include two level tones: high (H) and low (L), and four contour tones: falling (F), rising (R), falling-rising (FR), and rising-falling (RF). The amount of the linguistic data in this study and its description form a solid foundation for further investigation of this poorly documented language.